The Accountability of Officials Making Land Deeds (PPAT) Against Land Rights Grant Deeds Canceled by Courts - Habibi, Hilman (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the accountability of the official who made the land deed (PPAT) for the grant deed which was canceled by the court. The research approach method used in this journal is the sociological juridical method. The specification of this research is using descriptive analysis, which is research that describes a situation or event and also draws general conclusions from the problems discussed. The type of data used in this research is primary data covering the 1945 Constitution; Basic Agrarian Act No. 5 of 1960 Government Regulation Number 37 of 1998, Government Regulation Number 24 of 1997, Land Agency Agency Regulation Number 1 of 2006, as well as secondary data containing books and other supporting documents. Methods of data analysis obtained from the results of library research, field research will be analyzed using qualitative descriptive research. Based on the research, it was concluded that the results of the research show that First: The responsibility of the Officer who made the land deed for the Grant Deed which was canceled by the case study court Case Number: 0362/Pdt.G/2016/PA.Kng is in the form of responsibility for the obligation to make the deed regulated in Per ka BPN Number 1 of 2006, PP number 37 of 1998, PP Number 24 of 1997 accountability can be civil, administrative or criminal.Keywords: Accountability; Canceled; Court; Grants.